2012
DOI: 10.1080/00958972.2012.719080
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, crystal structures, and spectroscopic properties of copper(II) complexes with 3,14-diethyl-2,6,13,17-tetraazatricyclo(16.4.0.07,12)docosane

Abstract: Cu(L)(NO 3 ) 2 ] (1) and [Cu(L)(H 2 O) 2 ](SCN) 2 (2) [L¼ 3,14-diethyl-2,6,13,17-tetraazatricyclo(16.4.0.0 7,12 )docosane] have been prepared and structurally characterized by single-crystal X-ray diffraction at 100 K. For these constrained macrocycle complexes, copper(II) exists in a tetragonally distorted octahedral environment with the four nitrogen atoms of the macrocyclic ligands and two oxygen atoms from either nitrate or water in axial positions. The macrocyclic ligands in both complexes adopt the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Recently we have reported on synthesis, structural, spectroscopy as well as biological activities of metal complexes containing macrocyclic and phendione ligands [20][21][22] O complexes with anionic surfactant SDS and to reveal the effect of these complexes on the micellar properties of SDS by the measurement of specific conductance, the most widely used method to locate the CMC's of ionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have reported on synthesis, structural, spectroscopy as well as biological activities of metal complexes containing macrocyclic and phendione ligands [20][21][22] O complexes with anionic surfactant SDS and to reveal the effect of these complexes on the micellar properties of SDS by the measurement of specific conductance, the most widely used method to locate the CMC's of ionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-N distances of 2.018 (3) and 2.049 (3) Å can be compared to related complexes in Table 3. [19]. The Cu1-OW bond was not perpendicular to the CuN4 plane, with actual N1-Cu1-O1W and N2-Cu1-O1W angles of 88.22 (11) and 95.89(11) • , respectively.…”
Section: X-ray Crystallographymentioning
confidence: 96%
“…For example, crystallographic analysis of [Cu(L 2 )](ClO4)2 revealed that the copper(II) ion was tetracoordinated in a square planar configuration somewhat distorted towards tetrahedral geometry [15] whereas the [Cu(L 3 )](ClO4)2•2CH3CN had a square planar geometry [16]. The structural and physical properties of the Cu(II) and Ni(II) complexes with macrocycles containing cyclohexane ring and ethyl group were also reported [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Selected geometric parameters (Å , ). (Choi et al, 2012). The relatively long axial bond in (I) is due to a combination of the Jahn-Teller effect, the low doping content of Cu 2+ and the strong inplane ligand field.…”
Section: Tablementioning
confidence: 98%